PENGARUH ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN, PENERIMAAN KAS, DAN PENGELUARAN KAS TERHADAP PENGENDALIAN INTERNAL - Yusnaldi, Yusnaldi (Journal of Industrial Engineering & Management Research, 2021)
This study aims to improve the existing accounting information system. Namely the implementation procedure that can oversee the sales accounting information system, supervise the cash receipt accounting information system properly, and supervise the cash disbursement process. This research method uses descriptivequantitative method, with nonprobability sampling technique, with respondents of employees of PT Surya David Susanto. Questionnaire distribution data by sampling 31 respondents. The techniques used are the Vaidity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regressio, and with the help of the Statistical Package for Social Science (SPSS 22). The results of this study are the T test results for the sales accounting information system variable, namely T count 1.789 < T table 2.051, so the hypothesis of the sales accounting information system variable has no effect on internal control, for the T test for the cash receipt accounting information system variable, namely T count 3,235 > T Table 2,051, the variable cash receipts accounting information system has an effect on internal control. To test the cash disbursement variable, namely T count 0.396 < T table 2.051, the cash disbursement accounting information system variable has no effect on internal control. While based on the results of the F test 12,545 > F table 2,95 showed the independent variables simultaneously affect the dependent variable